1996
DOI: 10.1558/ijsll.v3i1.176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a foreign speaker in forensic phonetics: a report

Abstract: . InABSTRACT Expert witnesses in phonetics find themselves more and more often in forensic situations in which they have to identify the voice of a speaker who does not speak their native language. Until recently, little has been known about the role which the nativelanguage background of the listener plays in such speaker identification tasks. In this report, several aspects of an experimental investigation on the influence of native-language background on speaker identification are reviewed. Results of a fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 7 publications
3
21
0
1
Order By: Relevance
“…However, if hit and false-alarm rate were actually identical it would mean that discrimination sensitivity would be zero, Le., listeners were not able to discriminate targets from foils when voices were speaking Spanish. This would be an interesting result for the research presented in this paper as well as in Schiller and Koster (1996) and Koster and Schiller (1997).…”
Section: Speaker Identification Without Linguistic Informationsupporting
confidence: 55%
See 4 more Smart Citations
“…However, if hit and false-alarm rate were actually identical it would mean that discrimination sensitivity would be zero, Le., listeners were not able to discriminate targets from foils when voices were speaking Spanish. This would be an interesting result for the research presented in this paper as well as in Schiller and Koster (1996) and Koster and Schiller (1997).…”
Section: Speaker Identification Without Linguistic Informationsupporting
confidence: 55%
“…In a direct identification test, three different groups of listeners were asked to identify the voice of one speaker from a set of six different speakers (closed test). Listeners with a knowledge of German performed generally better than listeners without any knowledge of German (for details see Koster et al 1995;and Schiller and Koster 1996). We concluded that speaker identification involves not only purely phonetic information but also linguistic information.…”
Section: Speaker Identification Without Linguistic Informationmentioning
confidence: 69%
See 3 more Smart Citations